2018
DOI: 10.3897/zoologia.35.e14678
|View full text |Cite
|
Sign up to set email alerts
|

Testing camera traps as a potential tool for detecting nest predation of birds in a tropical rainforest environment

Abstract: ABSTRACT. Identification of the predators of bird nests is essential to test ecological and evolutionary hypotheses and to make practical management decisions. A variety of nest monitoring devices have been proposed but many remain difficult to set up in the field. The aim of this study was to test camera traps as a potential tool to study predation of natural nests in a tropical rainforest environment. Specifically, we registered the predators, assessed their size range, and we compared the use of one and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Electronic supplementary material The online version of this article (https://doi.org/10.1007/s43388-020-00027-w) contains supplementary material, which is available to authorized users. of other birds (Sick 1997;Cockle et al 2016;Ribeiro-Silva et al 2018). It is frequently found foraging in small groups (Guix et al 2001), but is rarely observed eating fallen fruits on the ground (Sick 1997).…”
Section: Communicated By: Lilian Manicamentioning
confidence: 99%
See 2 more Smart Citations
“…Electronic supplementary material The online version of this article (https://doi.org/10.1007/s43388-020-00027-w) contains supplementary material, which is available to authorized users. of other birds (Sick 1997;Cockle et al 2016;Ribeiro-Silva et al 2018). It is frequently found foraging in small groups (Guix et al 2001), but is rarely observed eating fallen fruits on the ground (Sick 1997).…”
Section: Communicated By: Lilian Manicamentioning
confidence: 99%
“…Several hypotheses indicate the most desired mineral by birds in clay soils is sodium (Powell et al 2009;Lee et al 2010;Sanders and Koch 2017), which cannot be sufficiently acquired through diet when part of the bird's usual food items are scarce (Sanders and Koch 2017). Red-breasted Toucans feed mostly on fruits, but their diet is richer in protein items as eggs, small vertebrates, and invertebrates (Leite et al 2010;Jesus et al 2012;Ribeiro-Silva et al 2018), which can provide enough sodium for its nutritional health. Another possibility for this geophagy event is the general mechanical function of bird gizzards, in which the ingestion of grits can aid in the grinding of food particles (Evans and Heiser 2004).…”
Section: Communicated By: Lilian Manicamentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their wide distribution, great mobility, and high sensitivity to environmental changes [ 1 ], birds have naturally become extremely important groups for monitoring. Time-lapse videos [ 2 , 3 ], camera traps [ 4 , 5 , 6 , 7 , 8 , 9 ], and unmanned aerial vehicle (UAV) [ 10 , 11 , 12 ] aerial photographs are widely used in bird monitoring. The advantages of using these devices are high security, long-term use, uninterrupted monitoring, minimal interference with birds, and surveying in areas where humans cannot easily stay for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Reliably identifying and studying nest predators elucidates the complex predator-prey systems, allowing researchers to indirectly infer nest predator behaviour (Croston et al, 2018), while exploring habitat, temporal, and climatic characteristics that might predict nest predation risk (Sperry et al, 2009, 2008; Sperry and Weatherhead, 2009). Studies monitoring nests through cameras (Ribeiro-Silva et al, 2018) and continuous recording video systems (Pierce and Pobprasert, 2007) suggest that snakes are major, widespread avian nest predators (DeGregorio et al, 2016a; Fritts and Rodda, 1998; Robinson et al, 2005). In order to fully understand the factors that facilitate interactions between avian nests and snakes, ecologists ought to study both groups individually and simultaneously (Weatherhead and Blouin-Demers, 2004).…”
Section: Introductionmentioning
confidence: 99%